Intensive IELTS reading. (TP.Hồ Chí Minh : Nxb.Tp Hồ Chí Minh : Nhân Trí Việt, 2013)
Introduction to IELTS reading; IELTS reading fundamentals; IELTS reading strategies; ...
IELTS Research Institute.
New oriental education & technology group.
Keywords: English language; IELTS; English language -- Study and teaching